The land without promise: the roots and afterlife of one biblical allusion - Kočí, Kateřina (Scriptural traces: critical perspectives on the reception and influence of the Bible, 2021)
Cover -- Title -- Copyright -- Acknowledgments -- Contents -- Introduction -- The Bible and literature -- Aims and methods -- Chapter 1 The Role of Artistic Interpretation in Biblical Hermeneutics -- The role of art in the hermeneutical process -- The text and the reader: partners in a dialogue -- The struggle between synchrony and diachrony -- Chapter 2 The Context and Reception of the Promised Land Motif in the Hebrew Bible and the New Testament -- A thematic analysis of the promised land in the Hebrew Bible -- An historical-critical analysis of Genesis 15.7 and Exodus 3.8 -- An historical-critical analysis of Genesis 15.1-21 -- An historical-critical analysis of Exodus 3.1-12 -- Reception of the promised land in the Hebrew Bible -- The Torah -- Deuteronomistic History -- The literary prophets to the end of the exile -- The postexilic era -- Reception of the promised land in the New Testament -- The Gospels and Acts -- The Pauline Epistles -- The non-Pauline Epistles -- Chapter 3 The Extra-Biblical and Post-Biblical History of the Promised Land Motif -- The history of biblical scholarship -- Antiquity -- Reformation -- Late tradition and application -- The history of literary scholarship -- Antiquity, the Middle Ages, and the Reformation -- Late reception and application -- The history of religious communities in the American Episcopal Church -- The community of New England Puritans -- The American Episcopal community of later centuries -- Chapter 4 Interpretations of the Promised Land Motif by Walter Brueggemann and John Steinbeck -- Brueggemann's interpretation of the promised land motif -- The land as symbol and fascinans -- Brueggemann's land symbolism: between landlessness and landedness -- Curing one's conscience but what comes next? Brueggemann and liberation theology -- John Steinbeck's interpretation of the promised land motif.